Towards Sustainable Transport and Mobility Perspectives on Travelling and Commuting in Small Island States - Kotzebue, Julia (Hamburg University Press, 2022)
Small island states are one of the most affected areas by sea-level rise, and sustainable transport development is crucial to their transition towards resiliency. However, their special spatial situations, insularity, geographic remoteness, small populations, and small economies resulted in high transport costs and car dependencies. The book moves away from the conventional focus on urban areas in the Global North and tourism. It gives a different perspective on sustainable transport, travelling, and commuting in the Caribbean and Europe. The authors provide research-based insights and show the state-of-the-art and future approaches for policy-makers, academics, and practitioners. Even beyond small island state research, the book offers an innovative outlook.